2021
DOI: 10.1021/acsearthspacechem.1c00148
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Destabilization in Salt-Containing Aqueous Reverse Micellar Colloidal Systems

Abstract: Colloidal systems, including micellar and reverse micellar mixtures, are essential for a variety of natural transport processes, such as the flow of organic and inorganic contaminants in lakes, rivers, and underground fissures. Thus, an understanding of their structure and stability is important for prediction of their behavior in complex environments. Previous experiments have shown that the solvodynamic diameters (D) of reverse micelles contract linearly with increased concentrations of salts such as NaBH4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…These results are consistent with previous characterizations of the commonly used CTAB RM system, though the R g values for the Br – pseudo-shell of the DLPC:DPC system here are about 25% smaller than those for CTAB RMs . Salt concentration is known to alter the size and stability in some RM systems . Comparative DLS measurements revealed that the high salt concentrations used to enhance the contrast in SAXS experiments lead to a slightly broader size distribution but do not significantly affect the RM size (Figure c).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with previous characterizations of the commonly used CTAB RM system, though the R g values for the Br – pseudo-shell of the DLPC:DPC system here are about 25% smaller than those for CTAB RMs . Salt concentration is known to alter the size and stability in some RM systems . Comparative DLS measurements revealed that the high salt concentrations used to enhance the contrast in SAXS experiments lead to a slightly broader size distribution but do not significantly affect the RM size (Figure c).…”
Section: Resultssupporting
confidence: 91%
“…60 Salt concentration is known to alter the size and stability in some RM systems. 61 Comparative DLS measurements revealed that the high salt concentrations used to enhance the contrast in SAXS experiments lead to a slightly broader size distribution but do not significantly affect the RM size (Figure 6c). Additionally, protein encapsulation results in a slight narrowing of size distribution but does not significantly change the RM size with GPx4 encapsulation and reveals a very slight size reduction (∼8%) with ubiquitin encapsulation (Figure 6d).…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…At w 0 = 10, the size of the reverse micelles appears to plateau as a function of w 0 rather than continuing to grow like those containing water. The size difference we observe is similar to observations when other salts are added to AOT reverse micelles. …”
Section: Resultssupporting
confidence: 86%
“…At least two factors likely cause surfactant counterions to reside largely at the interface: Coulombic attraction of counterions with the sulfonate headgroup and the inability of the water to screen charges from multiple cations within the water core. This insufficient screening can be interpreted in terms of the Debye screening length, which describes how far the electrostatic effect of a charge persists in solution. The Debye length is typically given by eq κ 1 = ε 0 ε r k B T 2 N A e 2 I where ε 0 is the permittivity of free space, ε r is the dielectric constant, k B is the Boltzmann constant, T is the temperature (K), N A is Avogadro’s number, e is the elementary charge, and I is the ionic strength of the solution.…”
Section: Discussionmentioning
confidence: 99%
“…25 Reactive uptake of volatile organics can lead to liquid−liquid phase separation 26 or the formation of highly viscous phases 27 in aerosols, while the salt content affects the size dependence of liquid−liquid phase separation 28 and the stability of reverse micelles when surfaceactive organics are present. 29 Ohno et al present a fluorescence-based aerosol flow tube technique for laboratory studies of liquid−liquid phase separation. 30 Adsorbed solutes can also influence ice nucleation in mineral dust.…”
mentioning
confidence: 99%